2011
DOI: 10.1111/j.1365-4632.2011.04967.x
|View full text |Cite
|
Sign up to set email alerts
|

Weekly vs. daily administration of oral methotrexate (MTX) for generalized plaque psoriasis: a randomized controlled clinical trial

Abstract: Nausea, vomiting, headache, and fatigue were significantly less common side effects in our patients who received MTX daily, but liver enzyme abnormalities were less common, and clinical efficacy was greater in the patients who received MTX weekly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The included studies randomized 1,352 patients, of whom 1,206 were included in the final analysis. The loss to follow-up was mainly attributable to one study, in which 305 patients were randomized but only 202 patients were analysed (12).…”
Section: Rct Search Results and Study Characteristicsmentioning
confidence: 99%
“…The included studies randomized 1,352 patients, of whom 1,206 were included in the final analysis. The loss to follow-up was mainly attributable to one study, in which 305 patients were randomized but only 202 patients were analysed (12).…”
Section: Rct Search Results and Study Characteristicsmentioning
confidence: 99%
“…Among them, nephrotoxicity has been regarded as one of the most important side effects. Compared to cyclosporine, the main side effects of methotrexate are irreversible liver cirrhosis, bone marrow suppression, and mucosal damage 13 . In addition, acute side effects such as elevation of liver enzymes are frequently reported during treatment with methotrexate 13 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to cyclosporine, the main side effects of methotrexate are irreversible liver cirrhosis, bone marrow suppression, and mucosal damage 13 . In addition, acute side effects such as elevation of liver enzymes are frequently reported during treatment with methotrexate 13 14 . In this study, abnormalities in AST/ALT were found in two patients (9.5%) while only one patient (4.8%) had an abnormality in uric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate (MTX) is one of the most clinically effective therapies used in the treatment of psoriasis . Clinical data from trials suggest that patients achieved 50–60% improvement in mean PASI at week 16–24 at a dosage of 15–19 mg weekly . However, patients may become resistant to MTX over time and increase in dosage can have serious side effects.…”
Section: Discussionmentioning
confidence: 99%